Activated platelet–T-cell conjugates in peripheral blood of patients with HIV infection: coupling coagulation/inflammation and T cells. (17th July 2015) - Green, Samantha A.; Smith, Mindy; Hasley, Rebecca B.; Stephany, David; Harned, Adam; Nagashima, Kunio; Abdullah, Shahed; Pittaluga, Stefania; Imamichi, Tomozumi; Qin, Jing; Rupert, Adam; Ober, Alex; et al.
Abstract : Background: Despite successfully suppressed viremia by treatment, patients with high levels of biomarkers of coagulation/inflammation are at an increased risk of developing non-AIDS defining serious illnesses such as cardiovascular diseases. Thus, there is a relationship between persistent immune activation and coagulation/inflammation, although the mechanisms are poorly understood. Platelets play an important role in this process. Although interactions between platelets and elements of the innate immune system, such as monocytes, are well described, little is known about the interaction between platelets and the adaptive immune system. Design: We investigated the interaction of a component of the coagulation system, platelets, and the adaptive immune system T cells. Methods: Healthy controls and combination antiretroviral therapy (cART)-treated HIV-infected patients with viral loads of less than 40 copies/ml for more than 15 months were analysed for platelet–T-cell conjugate formation. Results: Platelets can form conjugates with T cells and were preferentially seen in CD4 + and CD8 + T-cell subsets with more differentiated phenotypes [memory, memory/effector and terminal effector memory (TEM)]. Compared with healthy controls, these conjugates in patients with HIV infection were more frequent, more often composed of activated platelets (CD42b + CD62P + ), and were significantly associated with the D-dimer serum levels. Conclusion: These data support a model in which platelet–T-cell conjugates may play a critical role in the fast recruitment of antigen-experienced T cells to the place of injury. This mechanism can contribute in maintaining a state of coagulation/inflammation observed in these patients contributing to the pathology of the disease. Abstract : Supplemental Digital Content is available in the text